(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article systematized the factors that led to the digitization of data in the direction of human resource management of the bodies of the state customs service of the Republic of Uzbekistan and the stages of digitization to this day, and analyzed the indicators of the system’s efficiency today.